NOVEL PROTEIN STRUCTURE PRODUCED BY EFFECTIVE ANTIBODY USED FOR IMMUNIZATION - KAN, MING CHUNG (2016)
A method for enhancing an immune-response, the method comprising covalently bonding an amphiphilic peptide to an antigen to form an antigen complex compound, and administering the antigen complex compound to a subject. The antigen compound having an amphiphilic helical structure can enhance antigen delivery. L'invention concerne un procédé permettant d'amplifier une réponse immunitaire, le procédé comprenant les étapes consistant à lier de manière covalente un peptide amphiphile à un antigène pour former un composé complexe antigénique, et à administrer le composé complexe antigénique à un sujet. Le composé antigénique à structure hélicoïdale amphiphile peut augmenter la libération de l'antigène. 一种增进免疫应答的方法，其包含将两亲性肽共价结合至抗原以形成抗原复合体合成物，以及给予所述抗原复合体合成物予受试者。有着两亲性螺旋结构的抗原复合物，具有增进抗原递送的能力。